2016
DOI: 10.1097/aog.0000000000001263
|View full text |Cite
|
Sign up to set email alerts
|

Practice Bulletin No. 157

Abstract: The incidence of cervical cancer in the United States has decreased more than 50% in the past 30 years because of widespread screening. In 1975, the rate was 14.8 per 100,000 women. By 2011, it decreased to 6.7 per 100,000 women. Mortality from the disease has undergone a similar decrease from 5.55 per 100,000 women in 1975 to 2.3 per 100,000 women in 2011 (). The American Cancer Society (ACS) estimated that there would be 12,900 new cases of cervical cancer in the United States in 2015, with 4,100 deaths from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 52 publications
0
44
0
1
Order By: Relevance
“…In prior research, internists were found to be less compliant with cervical cancer screening guidelines than other providers (Corbelli et al, 2014). Similarly, internists in the present study more often recommended primary HPV testing annually or every 2 years for women of all ages (despite SGO/ASCCP interim guidance and ACOG recommendations that primary HPV testing be administered every 3 years and reserved for women ≥25 years (Huh et al, 2015; American College of Obstetricians and Gynecologists, 2016)). It should also be noted that more than half of internists (55.9%) who participated in the 2015 DocStyles survey on which the present study was based were excluded from the analyses because they did not perform cervical cancer screening.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…In prior research, internists were found to be less compliant with cervical cancer screening guidelines than other providers (Corbelli et al, 2014). Similarly, internists in the present study more often recommended primary HPV testing annually or every 2 years for women of all ages (despite SGO/ASCCP interim guidance and ACOG recommendations that primary HPV testing be administered every 3 years and reserved for women ≥25 years (Huh et al, 2015; American College of Obstetricians and Gynecologists, 2016)). It should also be noted that more than half of internists (55.9%) who participated in the 2015 DocStyles survey on which the present study was based were excluded from the analyses because they did not perform cervical cancer screening.…”
Section: Discussionmentioning
confidence: 90%
“…This result was surprising given the recency of SGO/ASCCP (Huh et al, 2015) and ACOG (American College of Obstetricians and Gynecologists, 2016) recommendations for primary HPV testing, and the absence of guidelines on this screening strategy from ACS (Saslow et al, 2012) and USPSTF (US Preventive Services Task Force, 2012). However, prior national surveys of US providers found widespread agreement that the HPV test administered alone is an effective screening modality in 2012 (79.5%–91.8%, depending on provider specialty) and 2009 (75.3%–86.1%) (Cooper and Saraiya, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations